Guidelines for Public Private Partnerships Compendium - Planning Commission (Planning Commission, 2004)
Several initiatives were taken by the Central Government in the mid-1990s for attracting private participation in different infrastructure sectors. This included creation of an enabling policy and regulatory framework, besides amendment of several laws. These efforts were intensified in 2004, following constitution of the Committee on Infrastructure (CoI) chaired by the Prime Minister.
Government of India
Planning Commission Government of India